Hubungan Antara Kepekaan Humor dengan Stres Kerja pada Pegawai Balai Karantina Pertanian Kelas I Semarang Jawa Tengah - Arini Widyowati Endy; Pungkas Priambodo (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2016)
This study aims to identify the correlation between sense of humor and employes job stress. This research involved 52 employes in The First Class of Agricultural Quarantine, Semarang, Central Java. Job stress scale and sense of humor scale were used to collect the data and the result was analyzed using the product moment correlation that was calculated by SPSS 15.0 for windows. The results showed that there were a significant relationship between sense of humor and job stress with a correlation coefficient r = -0.423 at significance level (p) 0.002 (p < 0.01). The higer individual sense of humor level, the lower employee job stress level and vice versa. Sense of humor give effective contribution of 17.90% to employee job stress. This result will be discussed further in this paper.Â Keywords: Job Stress, Sense of Humor